Karakteristik Litologi dan Zonasi Alterasi Hidrotermal Sistem Epitermal Sulfidasi Tinggi pada Daerah Pit X PT. J Resources Bolaang Mongondow - Yunir Tulong; Indriati Martha Patuti; Ayub Pratama Aris (Universitas Negeri Gorontalo, 2026)
Pit X of PT J Resources Bolaang Mongondow is a mineral prospect area that exhibits geological characteristics associated with a high-sulphidation epithermal system. This study aims to identify the lithological characteristics and hydrothermal alteration zoning developed within the study area through the integration of geological mapping, petrographic analysis, and Analytical Spectral Device (ASD) spectral analysis. The results indicate that the study area is composed of four lithological units, namely diatreme breccia, tuff, volcanic dacite, and volcanic andesite. Geological structures are dominated by joints trending northwest–southeast to north–south, which act as pathways for hydrothermal fluid circulation and influence alteration distribution. Based on ASD and petrographic analyses, four hydrothermal alteration zones were identified: vuggy silica zone (±7%), massive silica zone (±29%), advanced argillic zone (±31%), and argillic zone (±33%). The alteration assemblages consist of alunite, pyrophyllite, dickite, kaolinite, illite, and smectite. The spatial distribution of these alteration zones reflects progressive changes in the physicochemical conditions of hydrothermal fluids from proximal to distal parts of the system. The occurrence of vuggy silica and advanced argillic alteration, together with characteristic alteration mineral assemblages, indicates the development of a high-sulphidation epithermal system within the study area. These findings provide important information regarding lithological characteristics and hydrothermal alteration patterns that can be utilized to support geological interpretation and mineral exploration in the area.